2016
DOI: 10.1016/j.drugalcdep.2016.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of prescription opioid residue injection

Abstract: Background: There is growing evidence of intravenous administration of prescription opioids (POs) in several countries. Preparation of POs for injection may leave residues in containers and filters used by people who inject drugs and may lead to adverse health outcomes if they are injected.Methods: This exploratory study used cross-sectional data from the COSMO study, a prospective cohort of out-of-treatment cocaine users carried out in Montréal (Canada) between October 2010 and August 2015. For this analysis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…However, in our study, cases (PWID IE+) were more likely to have stable housing compared to controls. This is supported by Roy et a.l (16), who found that unstable housing was not associated with conducting multiple washes (utilizing residual drug for multiple injections), which is often the preparatory method used to inject prescription opioids, such as hydromorphone-CR. We hypothesize that PWID using hydromorphone-CR, which is a more costly illicit substance, can be associated with stable housing, which is reflective of financial stability.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…However, in our study, cases (PWID IE+) were more likely to have stable housing compared to controls. This is supported by Roy et a.l (16), who found that unstable housing was not associated with conducting multiple washes (utilizing residual drug for multiple injections), which is often the preparatory method used to inject prescription opioids, such as hydromorphone-CR. We hypothesize that PWID using hydromorphone-CR, which is a more costly illicit substance, can be associated with stable housing, which is reflective of financial stability.…”
Section: Discussionmentioning
confidence: 78%
“…Prescription rates for hydromorphonecontrolled-release (CR) (Hydromorph Contin ®, Purdue Pharma, Pickering, Ontario) in London are in the top quartile in Ontario (4,13,15). Furthermore, studies have shown that the misuse of prescribed opiates such as hydromorphone-CR amplify risk of infections due to the nature of how these substances are prepared for injection (11,(16)(17)(18). Hydromorphone-CR is difficult to dissolve in solution, often requiring PWID to use unsterile methods to prepare injectates.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prescription rates for hydromorphone controlled-release (CR) (Hydromorph Contin ®, Purdue Pharma, Pickering, Ontario) in London are in the top quartile in Ontario (4,13,15). Furthermore, studies have shown that the misuse of prescribed opiates such as hydromorphone-CR amplifies the risk of infections due to the nature of how these substances are prepared for injection (11,(16)(17)(18). Hydromorphone-CR is difficult to dissolve in solution, often requiring PWID to use unsterile methods to prepare injectates.…”
Section: Introductionmentioning
confidence: 99%